Perancangan dan Analisis Kinerja Steganography pada MPEG SAOC Menggunakan Improved Spread Spectrum - Aggrivina Dwiharzandis; Amirul Luthfi; Ikhwana Elfitri (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Object-based audio technology is important for audio reproduction because of providing the users with an ability to change the audio composition. As a result, MPEG Spatial Audio Object Coding (SAOC) as an international standard for encoding object-based audio has been widely used in many applications. However, the object-based audio transmission scheme is different than conventional audio transmission technology, so the use of steganography in MPEG SAOC needs to be further studied. In this work, a steganography technique has been developed based on Improved Spread Spectrum (ISS). There are two embedding configurations used in this study: embedding on MPEG SAOC audio objects and embedding on MPEG SAOC downmix signals. The performance of these two embedding configurations was analyzed by measuring ISS embedding capacity. As a comparison to the ISS method on channel-based audio, the ISS is also applied to Advanced Audio Coding (AAC). Based on the experiments, the embedding capacity of both proposed configurations varies depending on the bandwidth of audio signals. However, the downmix signal has a capacity of 20% higher than the audio objects. Moreover, the ISS embedding capacity on the MPEG SAOC downmix signal is similar to the embedding capacity on the AAC.